2001
DOI: 10.1007/s007840000085
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and arecoline mechanisms in human gingival fibroblasts in vitro

Abstract: Betel nut chewing, like cigarette smoking, is a popular oral habit which impinges on the daily lives of a population of approximately 200 million. People who chew betel nuts have a higher prevalence of periodontal diseases than those who do not. Many of the undesirable effects of betel nuts have been attributed to arecoline, a major component of the particular alkaloid in betel nuts. In this in vitro study, we have focused on the effects of arecoline and the role it could play in periodontal breakdown via its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 20 publications
5
33
0
1
Order By: Relevance
“…Arecoline exhibited cytotoxicity at the concentrations higher than 80 µg/ml. Similar studies were reported previously that arecoline had no effects on the cell proliferation in lower doses and inhibited cell growth in higher doses in human gingival fibroblasts [30] and human buccal fibroblasts [31]. Oxidative stress was cited as an important role in promoting cytotoxicity and previous studies have demonstrated that elevated oxidative stress could contribute to carcinogenesis in many type cancer cells [8], [9].…”
Section: Discussionsupporting
confidence: 81%
“…Arecoline exhibited cytotoxicity at the concentrations higher than 80 µg/ml. Similar studies were reported previously that arecoline had no effects on the cell proliferation in lower doses and inhibited cell growth in higher doses in human gingival fibroblasts [30] and human buccal fibroblasts [31]. Oxidative stress was cited as an important role in promoting cytotoxicity and previous studies have demonstrated that elevated oxidative stress could contribute to carcinogenesis in many type cancer cells [8], [9].…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, the expression of p53 regulated p21 (WAF1) and p53 activated DNA repair were repressed by arecoline [87]. Arecoline was cytotoxic to HGF cells due to depletion of intracellular thiols and inhibition of mitochondrial activity and induced cell cycle arrest in HGF cells at G2/M phase in a dose dependent manner [88]. Global gene expression profiling in HGF exposed to arecoline revealed that four genes related to maintenance of genome stability and DNA repair were repressed by arecoline [89].…”
Section: Resultsmentioning
confidence: 99%
“…At a concentration of 10 and 100 μg/mL the P21 fraction slightly (but not statistically) and markedly (and statistically p < 0.05) inhibited the cell growth (92.2% ± 3.5% relative to the control (Figure 4). Thus, P21 can decrease or obstruct mitochondrial function leading to insufficient energy levels in the human gingival fibroblast cells for their repair and regeneration (Chang et al, 2001;Issa et al, 2008). Certainly the polysaccharide arecoline is reported to be cytotoxic to human gingival fibroblast cells by inhibiting the mitochondrial function (Chang et al, 2001), where 50-200 μg/mL arecoline can inhibits 16-56% of mitochondrial activity.…”
Section: Cell Proliferation Activity Of P11 and P21mentioning
confidence: 99%
“…Thus, P21 can decrease or obstruct mitochondrial function leading to insufficient energy levels in the human gingival fibroblast cells for their repair and regeneration (Chang et al, 2001;Issa et al, 2008). Certainly the polysaccharide arecoline is reported to be cytotoxic to human gingival fibroblast cells by inhibiting the mitochondrial function (Chang et al, 2001), where 50-200 μg/mL arecoline can inhibits 16-56% of mitochondrial activity. Given that here P21 at 100 μg/mL appeared to inhibit around 90% of mitochondrial activity (Figure 4), then P21 would appear to be a significantly more efficient inhibitor than arecoline.…”
Section: Cell Proliferation Activity Of P11 and P21mentioning
confidence: 99%